Rotten Spring: An Auto-Ethnography of Power Dynamics in a Performance Art Collective - Traub, Sophie (Contingent Horizons: The York University Student Journal of Anthropology, 2019)
From an auto-ethnographic perspective, this article describes the power dynamics that played out in a process-focused collaboration between five artists. Working with an attempted non-hierarchical model of collaboration, various strategies for negotiation emerged in the absence of a focused leader, and this article focuses on three instances of acutely potent power dynamics as they emerged within the negotiation processes. Contributing to the discourse surrounding performance ethnography—which at once frames group dynamics as a performance to support fieldwork analysis, as well as examines performance creation as a method of fieldwork (among other methods and frameworks)–this paper presents a non-hierarchical collaborative process as a performance ethnography in which all participants were ethnographers, as the emphasis of the process and the attention of the collaborators was placed on the group dynamics rather than the creation of the final performance. This article frames the aesthetic of the social as emergent through instances of shifting power in the group.